Vacuum deposition onto webs, films, and foils - Bishop, Charles A. (William Andrew Pub., 2007)
This new book from William Andrew Publishing is the only practical reference available for anyone employing the roll-to-roll deposition process. Vacuum Deposition onto Webs, Films and Foils is an expansive journey of the process; benefiting manufacturing efficiency, unit cost reduction, and financial results. It is a sweeping approach to the total design of the vacuum deposition process written by a successful and world renowned consultant with three decades of experience. Roll-to-roll deposition processing is a high growth industry and this reference covers a wide variety of important industrial products that use vacuum deposited coatings, including: optical storage devices, metallized packaging films, energy conservation windows, electronic information displays, and magnetic electronic article surveillance (EAS) tags among many others. This book is a must-have for roll-to-roll machine operators, process engineers, and research and development engineers throughout industry. The book provides a broad appreciation of roll-to-roll vacuum deposition systems and processes. It will encourage a more comprehensive look from material supply through to the downstream processes that the product will encounter. It is a truly unique reference written to guide operators and engineers as an onsite consultant would.
Keywords: Vapor-plating.; Vacuum technology.; Surfaces (Technology); elektronické knihy; electronic books